IMD World Competitiveness Rankings - Dermot P. Coates; Rory Mulholland; Keith Fitzgerald (National Competitiveness and Productivity Council (NCPC), 2023)
Ireland is ranked 2nd out of 64 economies in the IMD's World Competitiveness Yearbook 2023, gaining nine places from 2022. Amongst the euro area countries, Ireland is ranked the most competitive, an improvement of two places since last year. Ireland improved its ranking across all four major competitiveness pillars: Economic Performance and Government Efficiency, Business Efficiency, and Infrastructure.
Keywords: 330